Figurative Language in the English Voice Line of Zhongli from Genshin Impact - Putri Delima (ELT Forum: Journal of English Language Teaching, 2025)
Narrative immersion in games is thrilling and full of metaphorical language, with the goal of clarifying character characterization in order to leave an impact on players. This study looks at the usage of figurative language in the English voice dialogue of Zhongli, one of the Archons in Genshin Impact, to identify major categories and explain their rhetorical purposes. A qualitative content analysis technique was used to examine and categorize 35 voice dialogues based on Harris' (2018) taxonomy of figurative language, which included metaphor, metonymy, simile, personification, and allusion. The results show that metaphor is the most frequently used method, stressing themes of order, permanence, and memory. In addition, the study emphasizes how additional rhetorical strategies, like comparison and symbolism, promote Zhongli's philosophical character and expertise while also reinforcing the game's world-building. By comparing the research findings to previous studies conducted by Azzahra (2024) and Lie & Tedjaatmadja (2024), this study demonstrates that Zhongli's figurative expressions are specifically tailored to his character identity, presenting deeper interpretive value beyond structural categorization.